Aniołowie (dobrzy i źli) w alegorycznej interpretacji Ksiąg Rodzaju, Wyjścia i Kapłańskiej w homiliach św. Cezarego z Arles - Pochwat, Józef (Vox Patrum, 2023)
Saint Caesarius of Arles (470-543), a great preacher, priest, lover of Sacred Scripture, organizer of the Church and monastic life in Gaul, left us writings that have not lost their value to this day. His teaching on angels (good and bad) based on the allegorical exegesis of the books of Genesis, Exodus and Leviticus can serve today’s believers. The author shows the blessed fruits of human cooperation with angels and, at the same time, the danger of submitting to temptations cleverly suggested by the devil. Caesarius’ exegesis is Christ-Centered, the author shows the unity of Bible; the Old Testament is fulfilled in the New Testament. The aim of this article is to present Caesarius’ views on the good and bad angels on a base of his homilies in which he uses allegorical interpretation of the above mentioned books of the Scripture.